MODEL FOR QUANTITATIVE ASSESSMENT OF RETURNING COLLECTOR-DRAINAGE WATER FROM IRRIGATED AREAS OF ARID ZONES - F. Kh. Khikmatov , G. Kh. Yunusov , B. E. Adenbaev , R. R. Ziyaev, N. B. Erlapasov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper is devoted to study of the dependence of returned collector-drainage water from large irrigated arias on the volume of water withdrawal for irrigation purposes and the total crop areas. The problem was solved on the example of irrigated lands of the Bukhara region. As a result of statistical estimation, equations of normalized regression were obtained. They are characterized by rather high values of the full coefficients of multiple correlation. Based on these equations, the calculated nomogram was expressed. Accuracy of the nomogram was analysed. The results showed that it can be used both for estimation and for forecasting collector-drainage flow from large irrigated areas of arid zones.